Polotsk, Vilnius, Moscow… Poetic and Biographical Wanderings of Oleg Minkin - Kowalow, Siergiej (Poznańskie Studia Slawistyczne, 2022)
In the context of the ideas of geopoetics, the article examines the images of three cities—Polotsk, Vilnius, Moscow—in the work of the famous Belarusian poet Oleg Minkin. Poems from two poetic cycles are analyzed: Гарады (Cities) and Гастарбайт (Gastrbayt). Attention is drawn to such categories as biographical and cultural space, therapeutic landscape and nostalgic landscape, the influence of literary tradition on the image of the city and the influence of the cultural environment of the city on the national identity of the poet. In search of the genius loci of the three cities, Oleg Minkin portrays Polotsk as a city awakening its national identity, a space of hope, Vilnius as a harmonious space for life and, at the same time, a place of nostalgia for the former glory of the Grand Duchy of Lithuania, and Moscow as a new Babylon, a mixture of languages and peoples, a space of concentrated longing and nostalgia for the homeland.